2022
DOI: 10.1182/bloodadvances.2022007773
|View full text |Cite
|
Sign up to set email alerts
|

Organ-specific response after low-dose interleukin-2 therapy for steroid-refractory chronic graft-versus-host disease

Abstract: Despite new therapeutic options, treatment of steroid-refractory chronic graft-versus-host disease (SR-cGVHD) remains challenging as organ involvement and clinical manifestations are highly variable. In previous trials of low-dose interleukin-2 (LD IL-2), we established the safety and efficacy of LD IL-2 for treatment of SR-cGVHD. In the present report, we combined 5 phase I or II clinical trials conducted at our center to investigate organ-specific response rate, co-involvement of organs, predictors of organ-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Although we are encouraged by our collective pediatric data, which now includes 24 pediatric patients with multiple years of follow-up, it has become increasingly difficult to obtain insurance approval for LD IL-2 because new small molecules have achieved FDA approval for second-line therapy of cGVHD. While our results reflect only single-center experience, LD IL-2 has consistently been shown as a safe and effective therapy with 105 adult and 11 pediatric patients 29 treated across 5 clinical trials with efficacy at least on par with the FDA-approved agents. It is our hope that a Children’s Oncology Group–sponsored trial of LD IL-2 for refractory cGVHD in children, currently in development (Carrie Kitko, personal communication, 30 March 2023), can help to establish efficacy in a multicenter setting and subsequently advance the approval status of LD IL-2 for this indication.…”
Section: Discussionmentioning
confidence: 64%
“…Although we are encouraged by our collective pediatric data, which now includes 24 pediatric patients with multiple years of follow-up, it has become increasingly difficult to obtain insurance approval for LD IL-2 because new small molecules have achieved FDA approval for second-line therapy of cGVHD. While our results reflect only single-center experience, LD IL-2 has consistently been shown as a safe and effective therapy with 105 adult and 11 pediatric patients 29 treated across 5 clinical trials with efficacy at least on par with the FDA-approved agents. It is our hope that a Children’s Oncology Group–sponsored trial of LD IL-2 for refractory cGVHD in children, currently in development (Carrie Kitko, personal communication, 30 March 2023), can help to establish efficacy in a multicenter setting and subsequently advance the approval status of LD IL-2 for this indication.…”
Section: Discussionmentioning
confidence: 64%
“…From 2007 through 2017, one hundred twenty-three adult patients and eleven pediatric patients with SR-cGVHD were enrolled on five IL-2 clinical trials at our institution ( 17 ). Fourteen patients were not evaluable for response and were excluded from further analyses.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown that overall Treg expansion and Treg phenotypes are similar between LD IL-2 responders and non-responders ( 18 ). A more recent organ-specific analysis of clinical and immune correlates of response to LD IL-2 in adult patients identify some early predictors of response such as higher Treg/Tcon ratio and lower terminal effector memory T cell counts within the first 4 weeks of therapy ( 17 ), but markers of continued response or disease progression during extended therapy have not been identified. Thus, predictive biomarkers to guide treatment duration for LD IL-2 and other second-line therapies remains an area of unmet need.…”
Section: Discussionmentioning
confidence: 99%
“…Among 105 evaluated patients ORR was 48.6% and 53.3% at 8 and 12 weeks, respectively. Reported organ-specific response was highest in liver (66.7%), gastrointestinal tract (62.5%), skin (36.4%), joint/muscle/fascia (34.2%), and lung (19.2%) [ 26 ].…”
Section: Methodsmentioning
confidence: 99%